The initial statement is: QS = SU (1)
QR = TU (2)
We have to probe that: RS = ST
Take the expression (1): QS = SU
We multiply both sides by R (QS)R = (SU)R
But (QS)R = S(QR) Then: S(QR) = (SU)R (3)
From the expression (2): QR = TU. Then, substituting it in to expression (3):
S(TU) = (SU)R (4)
But S(TU) = (ST)U and (SU)R = (RS)U
Then, the expression (4) can be re-written as:
(ST)U = (RS)U
Eliminating U from both sides you have: (ST) = (RS) The proof is done.
Answer:
14
Step-by-step explanation:
(a+b)^2
(a+b)(a+b)
FOIL
a^2 + ab+ab + b^2
Combine like terms
a^2 +2ab + b^2
Rearranging
a^2+b^2 +2ab
We know a^2+b^2 = 4 and ab= 5
4 + 2(5)
4+10
14
<u><em>Answer:</em></u>
Total fair of the two trips was $32.7
<u><em>Explanation:</em></u>
<u>We are given that the expression that taxi fair is:</u>
2.85 + 2.7M where M represents the number of miles
<u>1- For Thursday:</u>
Number of miles covered = M = 6 miles
<u>Substitute with M=6 in the given equation to get the fair on Thursday as follows:</u>
Fair on Thursday = 2.85 + 2.7(6) = $19.05
<u>2- For Friday:</u>
Number of miles covered = M = 4 miles
<u>Substitute with M=4 in the given equation to get the fair on Friday as follows:</u>
Fair on Friday = 2.85 + 2.7(4) = $13.65
<u>3- The total fair:</u>
Total fair = fair on Thursday + fair on Friday
Total fair = 19.05 + 13.65 = $32.7
Hope this helps :)
Answer:
What is the wI-FI PASSWORD
Step-by-step explanation:
Friend me on
(2x+1)-1=0
Divide
2=0
Reitalizie
<em>2=0</em>
Reatomize
⊕∴∵
Reunatomize
2=0
It is not true
2=0
Yeeeeeeeeeer eeee ee e e we. we e e we e e eeeee e e e e e e e e e e e